1999
DOI: 10.1902/jop.1999.70.9.960
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Tissue Disposition of Azithromycin in Patients Affected by Chronic Inflammatory Periodontal Diseases

Abstract: The present results indicate a marked penetration of azithromycin into both normal and pathological periodontal tissues, suggesting that azithromycin represents a promising option in both adjunctive and prophylactic treatments of chronic inflammatory periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 25 publications
2
49
0
3
Order By: Relevance
“…Another explication was the fact that this patient was the only one treated with the macrolide antibiotic azithromycin. Blandizzi et al showed in 1999 that azithromycin penetrated into both normal and pathological periodontal tissues (46), suggesting elimination of the targeted periodontal pathogenic bacteria for this patient.…”
Section: Discussionmentioning
confidence: 94%
“…Another explication was the fact that this patient was the only one treated with the macrolide antibiotic azithromycin. Blandizzi et al showed in 1999 that azithromycin penetrated into both normal and pathological periodontal tissues (46), suggesting elimination of the targeted periodontal pathogenic bacteria for this patient.…”
Section: Discussionmentioning
confidence: 94%
“…It has been proven that the local concentration of some specifi c antibiotics mainly depends on gingival health status. Blandizzi et al (26) showed that after 3 days of administration of azithromycin (500 mg/day), its concentration in healthy gingiva reached to 3.3 -3.6 mg/kg and achieved a maximum concentration in 12 h after the last administration. Until day 4 -6, following the last administration, the concentration of azithromycin in healthy gum was signifi cantly higher than the plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Azithromycin shows good bacteriostatic in-vitro activity against a wide variety of micro-organisms found in the mouth, 30 with a broad spectrum of activity towards anaerobic bacteria as well as Gram-negative bacilli. 31 One of the problems associated with using systemic antimicrobials for the adjunctive management of odontogenic infections is patient compliance.…”
Section: Therapeutic Usesmentioning
confidence: 99%